Dakwah Islam dan Kearifan Budaya Lokal: Konsep dan Strategi Menyebarkan Ajaran Islam - Hendra, Tomi; Nur Adzani, Siti Amalia; Muslim, Kori Lilie (Journal of Da'wah, 2023)
Islamic Da'wah and local wisdom are the two complementary concepts that can contribute to the development of harmony and social welfare. Islamic Da'wah is an effort to convey the teachings of Islam to individuals and communities with the purpose of guiding them to the straight path and inspiring them to good way. Local wisdom encompasses the values, traditions and practices who comesthe part of a community's identity. It involves respect for the cultural heritage acquired from ancestors. Meanwhile, local wisdom can be enriched by Islamic preaching through the values of Islam itself. And with the synergy between Islamic preaching and local wisdom, the community can build a solid foundation to achieve social harmonization and welfare. Through these concepts, it helps in strengthening the awareness of positive local cultural values. Meanwhile, in this article, the research method was used a qualitative design